2007
DOI: 10.1016/j.ydbio.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Zscan4: A novel gene expressed exclusively in late 2-cell embryos and embryonic stem cells

Abstract: The first wave of transcription, called zygotic genome activation (ZGA), begins during the 2-cell stage in mouse preimplantation development and marks a vital transition from the maternal genetic to the embryonic genetic program. Utilizing DNA microarray data, we looked for genes that are expressed only during ZGA and found Zscan4, whose expression is restricted to late 2-cell stage embryos. Sequence analysis of genomic DNA and cDNA clones revealed nine paralogous genes tightly clustered in 0.85 Mb on mouse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
330
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(363 citation statements)
references
References 55 publications
17
330
2
3
Order By: Relevance
“…The presence of T-positive cells in ES cell colonies has also been reported (Suzuki et al, 2006). Recently, we have reported that a gene named Zscan4, which is expressed exclusively in 2-cell embryos and ES cells, shows heterogeneous expression in ES cells: only up to 10% of ES cells cultured in undifferentiated conditions express Zscan4 by in situ hybridization (Falco et al, 2007). We suspect the existence of other transcription-regulating genes that show similar expression patterns.…”
Section: Rationale For the Studysupporting
confidence: 55%
See 2 more Smart Citations
“…The presence of T-positive cells in ES cell colonies has also been reported (Suzuki et al, 2006). Recently, we have reported that a gene named Zscan4, which is expressed exclusively in 2-cell embryos and ES cells, shows heterogeneous expression in ES cells: only up to 10% of ES cells cultured in undifferentiated conditions express Zscan4 by in situ hybridization (Falco et al, 2007). We suspect the existence of other transcription-regulating genes that show similar expression patterns.…”
Section: Rationale For the Studysupporting
confidence: 55%
“…Zscan4, which encodes SCAN domain and four zinc-finger domains, was identified previously for the heterogeneous spot-in-colony expression pattern (Falco et al, 2007). Zscan4 is expressed exclusively in mouse 2-cell embryos and ES cells.…”
Section: Genes With Spotted Expression Patterns (Spot-in-colony Pattern)mentioning
confidence: 98%
See 1 more Smart Citation
“…Here, we demonstrate that Zscan4, a unique gene highly expressed at the zygotic genome activation stage [23], in combination with the Yamanaka factors, not only dramatically decreases DDR but also significantly promotes iPS cell generation. Zscan4 can stabilize the genomic DNA in the process of somatic reprogramming, probably via rapid enhancement of telomere lengthening, resulting in high quality iPS cells as demonstrated by TCA analyses.…”
Section: Introductionmentioning
confidence: 80%
“…Zscan4 gene contains a SCAN domain and four zinc finger domains, and three isoforms (Zscan4c, Zscan4d and Zscan4f) encode full-length open reading frames [23]. Zscan4 is expressed specifically in two-cell embryos [23] and transiently in ES cells [28], and plays important roles in preimplantation embryonic development [23] and in the maintenance of genomic stability in ES cells [28]. γ-H2AX was detected in reprogramming cells two days after MEFs were transduced with either OSKM or OSKM plus Zscan4f (OSKMZ) (Figure 2A).…”
Section: Zscan4 Improves Genomic Stability During Reprogrammingmentioning
confidence: 99%